PENTINGNYA REFERENCE AND MASTER DATA MANAGEMENT DALAM MENINGKATKAN INTEGRITAS DATA DI ORGANISASI - Dimas Halki Widana; Rifa Nabila Malay; Zahwatun Suhaibah Rangkuti; Nurbaiti (CV. KAMPUS AKADEMIK PUBLISING, 2025)
In the digitalization era, organizations face challenges in ensuring data integrity due to inconsistencies and data duplication. Reference and Master Data Management (MDM) serves as a solution to improve data quality, consistency, and operational efficiency. This study aims to analyze the role of MDM in enhancing data integrity, identify implementation challenges, and propose strategies that organizations can adopt. Although various studies have discussed the benefits of MDM, there is still a research gap regarding the strategic and policy aspects of its implementation. This research employs a literature analysis method with a qualitative descriptive approach to understand the concept, challenges, and opportunities of MDM implementation. The findings indicate that effective MDM implementation improves data accuracy, consistency, and governance but faces challenges in cross-system data integration and policy change management. The recommended strategies include optimizing MDM through strong data governance policies and adopting technologies that support more efficient data integration. This study is expected to serve as a reference for organizations in developing more effective and adaptive data management